Prevalence of dual sensory impairment in veterans: a rapid systematic review - Raza, Zara; Hussain, Syeda F.; Gomes, Renata S. M. (Frontiers in Rehabilitation Sciences, 2024)
Dual sensory impairment (DSI) is prevalent in the older population, but due to exposure to military-related risk factors, it is a particular problem for veterans, older and younger. This rapid review aimed to critically review and summarise the prevalence of DSI in military veteran populations, as well as any associative factors and outcomes that were assessed. This was done in accordance with the Preferred Reporting Items for Systematic Reviews (PRISMA) statement. Several databases (Scopus, Web of Science, AMED, CINAHL Plus, Ultimate, and MEDLINE via EBSCOHost) were searched and five studies were selected for final review. All studies provided a prevalence rate for DSI in a veteran sample. One study also looked at functional independence as an outcome. Three of the studies considered blast injuries and traumatic brain injury (TBI) by using samples from TBI patient populations. Overall, results of this review suggest that age and presence of TBI and/or exposure to blast may increase prevalence of DSI in veterans. Prevalence rates ranged from 5.0–34.6% but there are caveats. There is a lack of universal or standardised definition for DSI, making it difficult to determine true prevalence. Future research should also include veterans who may not be receiving support from Veterans Affairs, consider factors such as TBI aetiology and severity based on clinical measures, and utilise a more standardised definition for DSI based on clinical measures.